2004
DOI: 10.1074/jbc.m310281200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of Rac1 Generates Rac1b, a Self-activating GTPase

Abstract: Rac1b was recently identified in malignant colorectal tumors as an alternative splice variant of Rac1 containing a 19-amino acid insertion next to the switch II region. The structures of Rac1b in the GDP-and the GppNHp-bound forms, determined at a resolution of 1.75 Å, reveal that the insertion induces an open switch I conformation and a highly mobile switch II. As a consequence, Rac1b has an accelerated GEF-independent GDP/GTP exchange and an impaired GTP hydrolysis, which is restored partially by GTPase-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 50 publications
(59 reference statements)
10
92
0
Order By: Relevance
“…Hence, the Rac1b insert sequence may alter the intrinsic biochemical properties, as well as interaction with regulators and effectors. Consistent with this possibility, Matos et al (2003) and Fiegen et al (2003) determined that Rac1b possessed impaired intrinsic GTPase activity, yet it retained GAP responsiveness in vitro and in vivo. Thus, unlike the G12V or Q61L mutants of Rac1, Rac1b can still be inactivated by GAP activity.…”
Section: Introductionmentioning
confidence: 73%
“…Hence, the Rac1b insert sequence may alter the intrinsic biochemical properties, as well as interaction with regulators and effectors. Consistent with this possibility, Matos et al (2003) and Fiegen et al (2003) determined that Rac1b possessed impaired intrinsic GTPase activity, yet it retained GAP responsiveness in vitro and in vivo. Thus, unlike the G12V or Q61L mutants of Rac1, Rac1b can still be inactivated by GAP activity.…”
Section: Introductionmentioning
confidence: 73%
“…Rac1b, an alternative splice variant of Rac1, contains a 19-amino acid insert immediately behind the switch II region (residues 60 -76) of Rac1. This has been shown to be sufficient to disrupt effector interaction itself (19,30,57,58 Previous studies demonstrated that Ras causes activation of Rac and that Rac function is critical for Rasmediated growth transformation. In these studies, Rac function was blocked by use of a dominant negative Rac1(17N) mutant (11,12), which blocks RacGEF activation of Rac (59), or by NSC23766, a cellpermeable small molecule that can bind directly to Rac1 and prevent its activation by Rac-specific RhoGEFs (27).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting Rac1b protein fails to interact with Rho-GDI in cells and displays both an increased intrinsic nucleotide exchange activity and a decreased rate of GTP hydrolysis in vitro. Accordingly, Rac1b is isolated predominantly in the active GTP-bound state from cell lines (21)(22)(23)(24). Unexpectedly, several classic Rac signaling pathways including lamellipodia formation or the activation of PAK1 or c-Jun-NH 2 -kinase activities were not activated by Rac1b.…”
Section: Introductionmentioning
confidence: 98%